Novel ruthenium(ii) and iridium(iii) BODIPY dyes: insights into their application in photodynamic therapy in vitro. Issue 8 (8th July 2019) - Aksakal, Nuray Esra; Tanrıverdi Eçik, Esra; Kazan, Hasan Hüseyin; Yenilmez Çiftçi, Gönül; Yuksel, Fatma
Abstract : In this study, novel photosensitizers, ruthenium(ii ) and iridium(iii ) BODIPY metal complexes (Ru-BD andIr-BD ), have been developed for the photodynamic therapy (PDT) of cancer cells. Abstract : Organic–metal complexes are promising molecules for use in photodynamic therapy (PDT). The aim of this study was to investigate in vitro effects of novel Ru(ii ) and Ir(iii ) BODIPY complexes for PDT. These hybrid organic–metal molecules (Ru-BD andIr-BD ) have been synthesized via reactions of a BODIPY precursor (BD ) with a phenanthroline unit bearing Ru(ii ) (3 ) and novel Ir(iii ) (4 ) compounds. The crystal structures of the new distyryl BODIPY (BD ) and Ru(ii ) complex (3 ) are also reported. The photophysical and singlet oxygen generation properties ofRu-BD andIr-BD were investigated in comparison with unsubstituted BODIPY (BD ). Moreover, Ru-BD andIr-BD have been biologically evaluated in vitro in chronic myeloid leukemia and cervical cancer cell lines in terms of photodynamic therapy efficacy in the presence ofBD control. These complexes were not toxic in the dark but red light was needed to induce cell death. These data support the fact thatRu-BD could be accepted as a valuable photosensitizer-drug for further PDT treatment.